Management of the Parathyroid Glands During Preventive Thyroidectomy in Patients With Multiple Endocrine Neoplasia Type 2. Issue 4 (October 2015) - Moley, Jeffrey F.; Skinner, Michael; Gillanders, William E.; Lairmore, Terry C.; Rowland, Kathryn J.; Traugott, Amber L.; Jin, Linda X.; Wells, Samuel A.
Abstract : Objectives: Patients with multiple endocrine neoplasia type 2 (MEN2) have mutations in the RET protooncogene and virtually all of them will develop medullary thyroid carcinoma. Family members identified by genetic testing are candidates for preventive thyroidectomy. Management of the parathyroids during thyroidectomy is controversial. Some experts advocate total parathyroidectomy with autotransplantation, whereas others recommend preserving the parathyroids in situ. Methods: Between 1993 and 2000, we performed preventive thyroidectomies on 50 patients with MEN2A (group A). All patients had a central neck dissection (CND) combined with total parathyroidectomy and autotransplantation of parathyroid slivers to the nondominant forearm or to the neck. Between 2003 and the present, we performed 102 preventive thyroidectomies attempting to preserve the parathyroid glands in situ with an intact vascular pedicle (group B). Individual parathyroids were autotransplanted only if they appeared nonviable or could not be preserved intact. Central neck dissection was done only if the serum calcitonin was greater than 40 pg/mL. Results: Permanent hypoparathyroidism occurred in 3 (6%) of 50 patients in group A, compared with 1 (1%) of 102 patients in group B ( P  = 0.1). After total thyroidectomy, no patient in either group developed permanent recurrent laryngeal nerve injury or hyperparathyroidism. Immediate postoperative serum calcitonin levels were in the normal range (<5 pg/mL) in 100 of 102 patients in group B. No patients in either group have died. Oncologic follow-up of patients in group B is in progress. Conclusions: In patients with MEN2A treated by preventive total thyroidectomy routine total parathyroidectomy with autotransplantation and CND gives excellent long-term results. However, preservation of the parathyroids in situ during preventive thyroidectomy combined with selective CND based on preoperative basal serum calcitonin levels is an effective and safe alternative that results in a very low incidence of hypoparathyroidism.